DETERMINAN KEPUTUSAN INVESTASI DENGAN RISIKO BISNIS SEBAGAI VARIABEL INTERVENING - Arintha Arintha; Andry Priharta (Media Riset Bisnis Manajemen Akuntansi, 2025)
The health sector is one of the main pillars of Indonesia's economy, as good health forms the foundation of a productive society. Hospitals, as key institutions within the health sector, not only provide healthcare services but also contribute to the economy through job creation and investments. Data from Indonesia’s Central Bureau of Statistics (BPS) recorded that the health sector contributed 4.5% to Indonesia's Gross Domestic Product (GDP) in 2022, highlighting the sector’s strategic role in the national economy. This study aims to examine the effects of profitability, liquidity, capital structure, and dividend policy on hospital investment decisions, while considering business risk as a mediating variable.This research employed a quantitative approach. The sample consisted of 7 hospital companies listed on the Indonesia Stock Exchange from 2020 to 2024, selected using purposive sampling. Data analysis was conducted using panel data regression. The results indicate that profitability, capital structure, and dividend policy have no significant effect on hospital investment decisions. In contrast, liquidity has a significant and positive effect, indicating that cash availability is a key factor in driving investment. Additionally, liquidity positively affects business risk; however, business risk does not significantly influence investment decisions and does not mediate the relationship between profitability, liquidity, capital structure, and dividend policy on investment decisions. These findings suggest that hospital investment decisions are primarily driven by strategic needs such as service enhancement, medical technology development, and regulatory compliance rather than financial factors or business risks. The results imply that hospital management should focus more on liquidity management and strategic investment planning rather than merely prioritizing profitability or capital structure.Keywords: profitability, liquidity, capital structure, dividend policy, business risk,  investment decisions.